THE IMMUNODERMAL ASSAYS ILLUSTRATED - SHNAWA, IBRAHIM M S; ALSALAMY, ADNAN KA (THE IMMUNODERMAL ASSAYS ILLUSTRATED, 2025)
The text was organized in two parts, two sections, and seven chapters. The first three chapters covered the theoretical fundamentals. Part two is composed of four chapters that span through the immune skin testing of humans, rabbits, rats, and chickens. The text chapter writing style starts with; i-skin structure, ii-skin functions, iii-animal assignment, iv-skin sensitin, v-immune response nature, vi-the onsetting skin preparations, vii-interventions, viii-scoring parameter, ix-gross immunobiologic reactions, x-cellular immunobiologic reactions, xi-the experimental excerpts and xii-the photos. The most significant data is summarized in; tables, figures and photos. The photographs attached to the text illustrate tuberculosis tests in humans, semen contact allergy, mitogenicity and blastogenicity in chicken models.